TEUN A VAN DIJK'S CRITICAL DISCOURSE ANALYSIS ON KOMPAS.COM NEWS - Islamiyah, Hanifa Yuti; Hermaliza, Hermaliza (Universitas Islam Sumatera Utara (UISU), 2024)
Critical discourse analysis is the process of explaining a text (social reality) to individuals or groups who tend to pursue their goals in order to create a framework that must be achieved. Teun A. Van Dijk's theory states that the main emphasis of critical discourse analysis is on inequality and power dynamics in social phenomena. The formulation of the problem in this research is how Teun A. Van Dijk's critical discourse analysis is viewed from the dimensions of the text on Kompas.com news. The aim of this research is to describe the text dimensions of Teun A. Van Dijk's model in the context of online news on kompas.com. The data collection technique used is content analysis technique, while data analysis uses the Teun A Van Dijk model of critical discourse analysis approach. The data source in this research is the kompas.com website regarding three news texts about corruption cases. The news discussed reveals real examples of inequality, domination and power. The research results show that news has three text dimensions, namely macrostructure, superstructure and microstructure. Macrostructure is used to convey opinions, facts and explanations regarding corruption events that occur. The superstructure of the three news items that meet the requirements consists of introduction, body and conclusion. Microstructure contains several elements, including background, details, intent, presuppositions, sentence form, pronouns (pronominals he, his, her, and we), lexicon, graphics, and metaphors (figures of speech).